OPTIMALISASI LABA MELALUI PEMULIHAN PEMBIAYAAN BERMASALAH DAN HAPUS BUKU DI BANK BJB SYARIAH KCP SUMEDANG - Asen Ahman; Kosim Rusdi; Ayus Ahmad Yusuf (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2022)
Profit is often used as a measure to assess company performance. The elements that form part of profit are income and costs. Profits in Islamic banks can be obtained through expansion of fund distribution (financing), fee-based income and rescue of non-performing financing as well as recovery of write-off financing. The most significant profit optimization outside the main business of Islamic banks is obtained through the recovery of non-performing financing and write-offs.The concept of Miles and Huberman can be applied in determining steps to save or resolve non-performing financing and recover write-offs to acquire loss reserves into profit. Through data reduction and then presenting research data, conclusions can be drawn from the results of research analysis in the form of a chart or cycle of problem solving steps.Based on the financial data for 2019, 2020 and 2021 analyzed, it can be revealed steps and procedures for rescuing and resolving non-performing financing and recovering write-offs at Bank bjb Syariah KCP Sumedang. The results of the analysis are proven to be able to increase profits significantly, so that the profits obtained by the bank become more optimal.The implementation of an early warning system is also needed in the context of handling the financing portfolio through strengthening the financing decision committee and improving the quality of contracts as well as controlling and monitoring the quality of ongoing financing.